Influence of My Happy Route Game-Based Learning Media in Improving the Arabic Writing Skills at MTs Al-Mas'udy Mojokerto - Juliyana Juliyana; Nafi’ul Huda; Ninik Indrawati; Muqimah Liwais Sunnah; Muhammad Hafid (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Purpose- This research has the purpose to meaning is the application and influence of the My Happy Route game-based learning media in learning Arabic for class VIII students at MTs Al-Mas'udy. Design/methodology/approach- This study uses a pre-experimental design type of research in the form of one group pretest-posttest design so that it does not use the control class, only uses the experimental class. Findings/results – There is a significant effect before and after the implementation of the My Happy Route game media, which is 19%. Previously, the average student score was 67.03, but it increased to 86.71. Originality/value - As a teacher who is always required to be creative, this media is very good to use in teaching and learning activities, both indoor and outdoor. Paper type – Research paper